Teknik Retorik Penceritaan Hadis Naratif Sahih Al-Bukhari Berdasarkan Perawi Terpilih - Nurhasma Muhamad Saad; Zulkipli Bin Md. Isa; Yuslina Mohamed; Wan Moharani Mohammad; Muhammad Marwan Ismail (NUN Gemilang Enterprise, 2024)
Non-Indexed Publication